Public and Private Roles in Health : Theory and Financing Patterns - Musgrove, Philip (World Bank, Washington, DC, 2013)
The appropriate role of the state in health is complex both in economic theory and in practice. Theory identifies three reasons for state action: (i) public goods or services with large externalities (involving efficiency); (ii) poverty (involving equity); and (iii) failings peculiar to insurance markets for health care (where both inefficiency and inequity arise). The insurance domain presents the most costly and difficult problems, and explains why - in contrast tom other sectors - governments tend to finance an increasing share of health care as incomes rise. Regulation, mandates and provision of information are also crucial public instruments; public provision of care is less important.